Limot visualization of the struggles of growing old - De Guzman, Constancio C.
The thesis aims to produce an artwork that visually portrays the issues dealing with the struggles of the elderly. Visual narratives are employed to focus on the general theme of loss or deterioration as an aftermath of the ageing process in older adults and specifically the sense of loss in terms of cognitive function manifested in various forms such as memory impairment; odd behavior; loss of the sense of time; and difficulty in navigating familiar locations or spaces. All these struggles lead to what is commonly understood by the Filipino layman as limot, pagkalimot or forgetfulness that accompany old age. For the thesis work, a singular acrylic painting measuring 6 feet by 10 feet depicts the proponent's personal experiences as well as his close friends and relatives' similar experiences with pagkalimot. The painting is accompanied by an installation consisting of a rocking chair, a table with glass jars filled with dried medicinal herbs, and a voice recording of interviews related to experiences with older adults.